Metabolite Fingerprinting of Kersting's Groundnut [Macrotyloma geocarpum (Harms) Maréchal & Baudet] Seeds Using UPLC-qTOF-MS Reveals the Nutraceutical and Antioxidant Potentials of the Orphan Legume - Tsamo, Armelle Tontsa; Mohammed, Mustapha; Dakora, Felix Dapare (Frontiers in Nutrition, 2020)
The identification and subsequent quantification of phenolic compounds in plants is the first step towards harnessing their associated nutritional and health benefits. Due to their diverse phenolic compound compositions, grain legumes are known for their high nutritional and health values. The aim of this study was to assess the inter-variations in chemical composition, phytochemical content and antioxidant capacity of seed extracts from eight Kersting’s groundnut [Macrotyloma geocarpum (Harms) Marechal & Baudet] landraces. The chemical profiles were evaluated using UPLC-qTOF-MS. Total phenolics and flavonoids content were determined by the Folin-Ciocalteu and aluminium chloride methods, respectively. The antioxidant capacities in the forms of DPPH and ABTS were evaluated using spectrophotometric methods. Principal component analysis was used to define similarities/differences between the landraces. Based on untargeted metabolomics analysis, 57 metabolites were identified, with phenolics, triterpenes, fatty acids and sphingolipids being the most predominant. The results showed that the black seeded KG1 (Puffeun) had the highest total phenolic (9.44 mg GAE/g) and flavonoid (3.01 mg QE/g) contents, as well as antioxidant capacity (9.17 µg/mL and 18.44 µg/mL based on DDPH and ABTS assays, respectively). The concentrations of ferulic acid hexoside, procyanidin B2, eryodictyiol-7-rutinoside and quercetin pentoside ranged from 51.78 – 441.31, 1.86 – 18.25, 3.26 – 13.95 to 5.44 – 63.85 µg/mg, respectively. This study presents a useful report on the phytochemical characterization of Kersting's groundnuts and shows that the grains can be used as a source of nutraceuticals for human consumption.